2001
DOI: 10.1099/00207713-51-6-1969
|View full text |Cite
|
Sign up to set email alerts
|

Microbacterium gubbeenense sp. nov., from the surface of a smear-ripened cheese.

Abstract: Phenotypic and phylogenetic studies were performed on 11 strains of a Microbacterium-like organism isolated from the surface of a smear-ripened cheese. The isolates were Gram-positive, catalase-positive, facultatively anaerobic, oxidase-negative, non-spore-forming, non-motile, small, slender rods and grew in 12 % (w/v) NaCl. Chemotaxonomic investigation revealed that all the isolates belonged unambiguously to the genus Microbacterium. They contained type B1 peptidoglycans with L-lysine as the diamino acid and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…All the isolates in clusters 10 to 20 had identical PFGE patterns as those previously identified as C. mooreparkense DPC 5307 (cluster 11) and C. mooreparkense DPC 5313 (unclustered) and so are considered to be C. mooreparkense (1). Similarly, the isolates in clusters 21, 22, and 24 to 26 had PFGE patterns similar to those previously identified as M. gubbeenense DPC 5286 and DPC 5291 (cluster 21) and M. gubbeenense DPC 5281 (unclustered) (2). Cluster 23 contained C. variabilis NCDO 2097 and NCDO 2099.…”
Section: Microbiology Of Cheese Surfacesupporting
confidence: 53%
See 1 more Smart Citation
“…All the isolates in clusters 10 to 20 had identical PFGE patterns as those previously identified as C. mooreparkense DPC 5307 (cluster 11) and C. mooreparkense DPC 5313 (unclustered) and so are considered to be C. mooreparkense (1). Similarly, the isolates in clusters 21, 22, and 24 to 26 had PFGE patterns similar to those previously identified as M. gubbeenense DPC 5286 and DPC 5291 (cluster 21) and M. gubbeenense DPC 5281 (unclustered) (2). Cluster 23 contained C. variabilis NCDO 2097 and NCDO 2099.…”
Section: Microbiology Of Cheese Surfacesupporting
confidence: 53%
“…Therefore, a polyphasic approach to their identification, involving chemotaxonomic RAPD and PFGE, was used. This showed that, except for five isolates which were identified as C. flavescens, most (89%) of the 390 isolates from the inoculated and noninoculated cheese were either C. (1,2). Thirtyseven (9.3%) isolates were not identified.…”
Section: Discussionmentioning
confidence: 96%
“…The bacterial species selected for this experiment (Table 1) belong to diverse groups of bacteria frequently used in dairy fermentation and isolated as non-starter bacteria from cheese or from natural whey culture (Brennan et al, 2001;Mounier et al, 2007;Poga ci c et al, 2013;Montel et al, 2014;Gatti et al, 2014). Several curd- (Martin et al, 2001), and cheese-based media (Gori et al, 2012;Sgarbi et al, 2013) have already been developed for aroma characterization of microorganisms but differ in composition from our curd-based medium.…”
Section: Growth Of Varied Bacterial Species In the Curd-based Mediummentioning
confidence: 99%
“…During the last few years, the microflora of several smear cheeses has been extensively investigated and categorically identified using combinations of phenotypic and genotypic techniques (9,15,29,33,42). These studies have resulted in the identification of several new species of bacteria, including Arthrobacter arilaitensis and Arthrobacter bergerei (21), Agrococcus casei (6), Corynebacterium casei (7), Corynebacterium mooreparkense (8) (subsequently shown to be Corynebacterium variabile [18]), Microbacterium gubbeenense (8), Staphylococcus equorum subsp. linens (36), Staphylococcus succinus subsp.…”
mentioning
confidence: 99%
“…The aim of the present study was to investigate some of the growth characteristics of B. aurantiacum, C. variabile, S. saprophyticus, and two recently described new species, C. casei and M. gubbeenense (7,8), isolated from smear cheese. Particular attention was given to their ability to metabolize lactose, lactate, and amino acids and to the likely enzymes involved.…”
mentioning
confidence: 99%